A cost-effectiveness analysis of the prophylaxis versus on-demand regimens in severe hemophilia A patients under 12 years old in southern Iran. Issue 1 (1st January 2021) - Zahedi, Zohreh; Karimi, Mehran; Keshavarz, Khosro; Haghpanah, Sezaneh; Ravangard, Ramin
ABSTRACT: Objective: This study aimed to compare the cost-effectiveness of these two regimens in hemophilia A patients, under-12-years-old in southern Iran. Methods: A cost-effectiveness study comparing prophylaxis versus on-demand was conducted on 34 hemophilia patients (24 and 10 patients were on the prophylaxis and on-demand regimens respectively) in 2017. The Markov model was used to estimate the economic and clinical outcomes. The costs were collected from the societal perspective, and the utility criterion was the 'quality adjusted life year (QALY)' indicator. The required data were collected using a researcher-made cost checklist, the EQ5D standard questionnaire and Hemophilia Joint Health Score. The probabilistic sensitivity analysis (PSA) was performed to determine the robustness of the results. Results: The means of costs, joint health score and QALY in the prophylaxis regimen were 478, 963.1 purchasing power parity (PPP), 96.67, and 11.98 respectively, and in the on-demand regimen were 521, 797.2 PPP, 93.46 and 10.99 respectively. The PSA confirmed the robustness of the model's results. The results of the scatter plots and acceptability curves showed that the prophylaxis regimen in 97% of the simulations for the thresholds below 20950 PPP was more cost-effective than on-demand regimen. Conclusion: Prophylaxis regimen showed the lower costs and higher effectiveness and utility in comparison with the on-demand regimen. It is recommended that prophylaxis should be considered as the standard care for treatment of hemophilic patients.